Flux analysis of a novel dual rotor hybrid excitation flux switching machine (DRHEFSM) - Hassan, Muhammad Kamaluddin (Asian Research Publishing Network (ARPN), 2015)
Hybrid Excitation Flux Switching Machine (HEFSM) mainly utilizes Field Excitation Coil (FEC) and Permanent Magnet (PM) as main flux sources. The motor exhibits high performance compared to Permanent Magnet Flux Switching Machine (PMFSM) and Field Excitation Flux Switching Machine (FEFSM) because of its flux sources consist of both FEC and PM. The performance of HEFSM can be further improved by introducing Dual Rotor HEFSM (DRHEFSM). The DRHEFSM is designed in order to create high performance motor in terms of torque speed characteristic and efficiency. This newly design motor also has an advantage in controlling the rotor rotation whether for single rotor rotation, inner rotor or outer rotor as well as both rotor rotations. Moreover, when only outer rotor rotates, the outer stator active part produces flux and vice versa when only inner rotor rotates. The purpose of this paper is mainly to validate the operating principle of DRHEFSM in performing the three phase operating principle. It has been proven that the DRHEFSM can work properly by following the operating principle of three phase machine based on the analysis that has been conducted. This motor is expected to perform much better than the existing HEFSM motor